How moles walk; it's all thumbs. (30th October 2019) - Lin, Yi-Fen; Konow, Nicolai; Dumont, Elizabeth R.
Abstract : A recurring theme in the evolution of tetrapods is the shift from sprawling posture with laterally orientated limbs to erect posture with the limbs extending below the body. However, in order to invade particular locomotor niches, some tetrapods secondarily evolved a sprawled posture. This includes moles, some of the most specialized digging tetrapods. Although their forelimb anatomy and posture facilitates burrowing, moles also walk long distances to forage for and transport food. Here, we use X-ray Reconstruction Of Moving Morphology (XROMM) to determine if the mole humerus rotates around its long axis during walking, as it does when moles burrow and echidnas walk, or alternatively protracts and retracts at the shoulder in the horizontal plane as seen in sprawling reptiles. Our results reject both hypotheses and demonstrate that forelimb kinematics during mole walking are unusual among those described for tetrapods. The humerus is retracted and protracted in the parasagittal plane above, rather than below the shoulder joint and the 'false thumb', a sesamoid bone (os falciforme), supports body weight during the stance phase, which is relatively short. Our findings broaden our understanding of the diversity of tetrapod limb posture and locomotor evolution, demonstrate the importance of X-ray-based techniques for revealing hidden kinematics and highlight the importance of examining locomotor function at the level of individual joint mobility.